2011
DOI: 10.1258/jrsm.2011.110180
|View full text |Cite
|
Sign up to set email alerts
|

The answer is 17 years, what is the question: understanding time lags in translational research

Abstract: This study aimed to review the literature describing and quantifying time lags in the health research translation process. Papers were included in the review if they quantified time lags in the development of health interventions. The study identified 23 papers. Few were comparable as different studies use different measures, of different things, at different time points. We concluded that the current state of knowledge of time lags is of limited use to those responsible for R&D and knowledge transfer who face… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
1,439
3
24

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 2,228 publications
(1,589 citation statements)
references
References 54 publications
20
1,439
3
24
Order By: Relevance
“…A study by Morris et al has reported a lag of 17 years for research to impact clinical practice, with some public health research evidence even requiring more than half a decade to impact policy [26,27]. In contrast, we have reported effect on policy and/or practice within 2–3 years of the completion of the project.…”
Section: Discussioncontrasting
confidence: 60%
“…A study by Morris et al has reported a lag of 17 years for research to impact clinical practice, with some public health research evidence even requiring more than half a decade to impact policy [26,27]. In contrast, we have reported effect on policy and/or practice within 2–3 years of the completion of the project.…”
Section: Discussioncontrasting
confidence: 60%
“…Evidence-based medicine advocates bemoan the fact that new drugs and interventions take an average of 17 years to become mainstream. 4 Social media offer the opportunity to shorten this by years through increased connectivity. Is this not a good thing?…”
Section: Social Media Has Created Emergency Medicine Celebrities Whomentioning
confidence: 99%
“…The assimilation of research findings into medical practice often takes decades; estimates of the lag time between journal submission and use in routine practice cluster around 17 to 23 years. 1 Reducing the time to the integration of accepted knowledge has been an objective of many professional organizations and academic institutions with varying degrees of success.…”
Section: Introductionmentioning
confidence: 99%